The Model for Determining Rational Inventory in Occasional Demand Supply Chains - Evgenii.G. Anisimov; Murat R. Gapov; Evgeniia.S. Rodionova; Tatiana Saurenko (International Journal of Supply Chain Management, 2019)
In order to ensure continuous demand for products in cases where it is impossible or economically inexpedient to fully combine the product supply volume and terms with the moments of appearing demand for it in the occasional demand supply chains, the necessity for inventory appears. High cost of maintaining inventory and significant losses due to its deficit cause an important issue of determining the rational inventory in occasional demand supply chains. The article proposes a model for determining the rational inventory with a fixed period of its replenishment and occasional demand. The peculiarity of the model consists in taking into account the finite, but a priori unknown, quantity of consumers characteristic of real demand and using small samples to characterize the model parameters. It allows for more adequate, comparing to the traditional model use, determination of rational inventory of the products in the supply chains.